A parameterized automatic programming solution for composite grinding based on digital image processing - Shen, Nanyan; Zhao, Chen; Li, Jing; Xu, Yingjie; Wu, Yang; Deng, Zongqian (International journal of advanced manufacturing technology, 2020)
In this paper, a parameterized automatic programming solution whose advantage depends on the automatic feature recognition of digital image is proposed and applied to the development of automatic programming software for composite grinding. This solution can overcome the difficulty of recognizing intersecting feature of complicated rotational part. And a 7-layer CNN classifier is utilized to decide whether the part has the internal features or not, which makes the proposed feature recognition method more intelligent than retrieving the unknown objects blindly. The emphasis of the research is the geometric data extraction algorithm which is the synthesis of border following algorithm, corner detection algorithm and a variety of morphological processing. Under the condition of 12000 × 12000 pixel dimension and 200-dpi resolution of input image, the relative errors between the extracted and actual values of various geometric data are all less than 0.05% for the rotational parts of maximum diameter 500 mm and maximum length of 1500 mm. And all the extracted values of geometric data rounded to integers can fully meet the requirements of NC programming. The automatic programming software based on the proposed solution has excellent portability and practicability, which is independent of any CAD tools or data exchange standards. After the programs generated by the automatic programming software are validated in simulation software NCSIMUL, the software is integrated into HNC-848 CNC system and applied in the prototype of H377 composite grinding center.